Internal surface measurement of metal powder bed fusion parts - Thompson, Adam; Senin, Nicola; Maskery, Ian; Körner, Lars; Lawes, Simon; Leach, Richard (Elsevier, 2018)
Recent advances in X-ray computed tomography (XCT) have allowed for measurement resolutions approaching the point where XCT can be used for measuring surface topography. These advances make XCT appealing for measuring hard-to-reach or internal surfaces, such as those often present in additively manufactured parts. To demonstrate the feasibility and potential of XCT for topography measurement, topography datasets obtained using two XCT systems are compared to those acquired using coherence scanning interferometry and focus variation microscopy. A hollow Ti6Al4V part produced by laser powder bed fusion is used as a measurement artefact. The artefact comprises two component halves that can be separated to expose the internal surfaces. Measured surface datasets are accurately aligned and similarly cropped, and compared by various qualitative and quantitative means, including the computation of ISO 25178-2 areal surface texture parameters, commonly used in part quality assessment. Results show that XCT can non-destructively provide surface information comparable with more conventional surface measurement technologies, thus representing a viable alternative to more conventional measurement, particularly appealing for hard-to-reach and internal surfaces.